Phytoremediation By Aromatic Plants To Remove Heavy Metals From Contaminated Soil : Case Study Of Taiping Landfill - Mashhoor Rood, Maryam (2014)
Heavy metal pollution is a widespread occurrence that causes serious environmental problems. This issue has to be addressed to ensure a safe and clean environment. The use of plant species to remove contaminants from soils is generally described as phytoremediation. Phytoremediation is an environment-friendly and emerging technology that purges contaminated soil and water to a large extent. According to current research, instead of growing edible crops, growing certain aromatic species is feasible. The final product is free from heavy metals so that such aromatic crops are considered to be an excellent choice for phytoremediation. This study evaluates the potential application of thymus vulgaris, sweet basil. Origanum majorana, and portulaca oleracea in the phytoremediation of as, co. Cr, cu, li, mn, ni, pb. V. And zn. Seeds were planted in six different growth media pots, including sn1, sn4, sn8, nn1, nn2, and nn4, their levels in a completely randomized block design with three replications.